A dinâmica de ocupação provocada pela expansão urbana ao longo das rodovias GO-020 e BR-153 em Goiânia/GO - Di Simoni, Thais Valle (2023)
Urban sprawl is a globally prevalent phenomenon in metropolises that has brought about significant transformations in urban territories. Understanding the dynamics and establishing analysis patterns of these processes is crucial for proposing more equitable and sustainable growth guidelines in cities. In Goiânia, it is observed that urban sprawl has led to the occupation of peripheral areas with distinct characteristics in each part of the municipality. Thus, this study proposes an examination of the growth of the city of Goiânia by analyzing the expansion along the BR-153 and GO-020 highways in the Eastern Region, characterized by the massive presence of higher social classes through the construction of gated horizontal condominiums. The objective is to identify urban phenomena and their actors in the spatial production of this region, spatially characterized by conurbation and marginal occupation of highways, extending the dominance of gated communities beyond the municipal limits of Goiânia, reaching Senador Canedo. To achieve this purpose, the study employs documentary analysis, literature review, spatial analysis, statistical data analysis, and field research to identify the expansion pattern and the agents responsible for this production. Thus, it is observed that the metropolization consolidating in this region results from processes such as sprawled and segregated expansion, reinforced by the strong presence of gated communities for middle and high-income residents. This brings about tangible changes in the metropolis' landscape, imprinting distinctive characteristics on the socio-spatial dynamics in this region. Consequently, disparate spaces are produced in the surroundings, leading to the strengthening of conurbation, one of the first expressions of metropolization, which ultimately generates various urban problems.